The Better Angels of Our Nature: Why Violence Has Declined - Muhammad Fahmi Masdah (WIMAYA, 2022)
Pinker’s goal to provide evidence that accounts for the falling homicide and violent combat death rates in the modern world is insufficient and, more often than not, misguided. The main issue being his failure to set up a productive analytical approach that lives up to his remarkably overarching research question: today’s level of global violence is the lowest in history. While he has attempted to present the violence levels typically in the past by coupling empirical and archeological data of the prehistory mankind, he lacks the credibility to do so for mainly two reasons: the sheer limitation of archeological evidence prior to the development of modern nation-state along with his flawed statistical analysis, and his persistence to treat war mortalities as merely an empirical variable. Similarly, though this article makes only remote attempts to examine the actual trend in civilizational and cultural conflict over a longer time period, it has brought into attention the demand to incorporate constructivist approach into the study of violence in order to better comprehend its complexities which have been largely driven by the development in the new wars. For the reasons mentioned above, Pinker has and will continue to get the violence levels wrong, and the world is as violent as ever.